Elizabeth Barrett Browning's 'Aurora Leigh' : a Reading Guide. - Martinez, Michele C. (Reading guides to long poems., 2012)
Introduces new readers and students to a celebrated and controversial Victorian novel-poemMichele Martinez guides readers through the poem's major themes and literary and socio-cultural contexts, introducing a range of interpretive frameworks. Long extracts from the poem are accompanied by helpful explanatory commentary. The text's composition history, major influences and modes of poetic expression are also discussed. The teaching and bibliographic chapters offer supplementary materials including print and internet resources. Key Features *Ideal guide for readers coming to the text for the fir.